Characterization, modeling, and evaluation of geotechnical engineering systems - Ge, Louis (2014)
Geotechnical Special Publication 248 contains 13 peer-reviewed papers on the characterization, modeling, and evaluation of geotechnical engineering systems. Topics include: soils and rock instrumentation and modeling; foundation failure and repair; and embankments and ground subsidence. This GSP will be of interest to both researchers and practitioners in geotechnical engineering